2021
DOI: 10.1093/hmg/ddab112
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic tirasemtiv treatment improves in vivo and in vitro muscle performance in actin-based nemaline myopathy mice

Abstract: Nemaline myopathy, a disease of the actin-based thin filament, is one of the most frequent congenital myopathies. To date, no specific therapy is available to treat muscle weakness in nemaline myopathy. We tested the ability of tirasemtiv, a fast skeletal troponin activator that targets the thin filament, to augment muscle force—both in vivo and in vitro—in a nemaline myopathy mouse model with a mutation (H40Y) in Acta1. In Acta1H40Y mice, treatment with tirasemtiv increased the force response of muscles to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…It is known that tirasemtiv (Tir) binds specifically with high affinity to TN but does not interact with actin, myosin, or Tpm [ 55 ], so it can be used as a specific activator of calcium activation in skinned skeletal muscle fibers [ 56 , 57 , 58 ]. In addition, it was previously shown that the troponin activator CK-2066260, a structural analog of tirasemtiv, can correct the low calcium sensitivity of sarcomeres induced by the point mutation [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that tirasemtiv (Tir) binds specifically with high affinity to TN but does not interact with actin, myosin, or Tpm [ 55 ], so it can be used as a specific activator of calcium activation in skinned skeletal muscle fibers [ 56 , 57 , 58 ]. In addition, it was previously shown that the troponin activator CK-2066260, a structural analog of tirasemtiv, can correct the low calcium sensitivity of sarcomeres induced by the point mutation [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…NM is characterized by muscle weakness and diminished muscle size due to muscle atrophy. Both of these characteristics have also been observed in animal models with mutations in NEB or ACTA1 (encodes skeletal muscle α-actin) [ 22 , 23 , 34 , 35 , 36 ]. The molecular mechanism underlying the muscle weakness is likely to include alterations in the contraction mechanism due to mutations in the sarcomeric proteins that disrupt the normal cross-bridge behavior [ 6 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Например, тирасемтив, быстрый активатор скелетного тропонина, действующий на тонкие нити, продемонстрировал свою эффективность в качестве средства, которое увеличивает мышечную силу и может быть применено для компенсации гипотонии при мышечной дисфункции. В исследованиях на генетически-модифицированных мышах и клетках пациента с немалиновой миопатией, несущих мутацию актина (ACTA1H40Y), лечение тирасемтивом увеличивало инотропные показатели до показателей сравнимых со здоровым контролем [118].…”
Section: средства с положительным влиянием на мышечную силуunclassified